Adventism on the Northwestern frontier - Johnson, Doug R. (Oronoko Books, 1996)
Why would 19th century Adventists leave the safety of their homes to join thousands of determined settlers trudging across the dangerous Oregon Trail? This is a fascinating account of how Seventh-day Adventism slowly gained a foothold and spread in this wild hinterland. - Foreword; Preface; 1. The Northwest's First Adventist; 2. He Couldn't Hide from the Sabbath; 3. A Missionary for the Northwest; 4. The Upper Country; 5. The Willamette Valley; 6. Ellen White Visits the Northwestern Frontier; 7. William Nichols; 8. New Leaders for the Northwest; 9. The Crisis of 1884; 10. The West Side; 11. Puget Sound; 12. The Inland Empire; 13. Father and Son; 14. Snake River Adventism; 15. Reading, Writing, and Arithmetic; 16. Conard Hall--The Rest of the Story; 17. Big Sky Country; 18. The Story Uncle Arthur Got Wrong; 19. Kellogg's Health System/Northwest; 20. The Germans and Scandinavians; 21. Evangelism in the Wild West; 22. Frontier Religion; Photographs; References; Notes